An investigation of factors affecting progress of patients on a stroke unit. Issue 4 (April 1989) - Lincoln, N B; Blackburn, M; Ellis, S; Jackson, J; Edmans, J A; Nouri, F M; Walrer, M F; Haworth, H
Abstract : The aim of the study was to identify factors affecting the progress in physical abilities and activities of daily living of patients admitted to a stroke unit. A series of 70 patients admitted consecutively were assessed on a series of tests of motor, functional and cognitive abilities at admission. They were assessed for level of motor abilities and activities of daily living at discharge and 9 months after stroke. Predictive equations were developed which account for between 61% and 33% of the variance in motor abilities and activities of daily living at discharge and at 9 months after stroke. The most important factor influencing outcome was the degree of motor loss.